Preclinical and subclinical events in motor neuron disease. Issue 2 (February 1988) - Swash, M; Ingram, D
Abstract : It is suggested that in motor neuron disease there is a long preclinical period of relative tolerance and compensation before presentation with apparently focal features. During this phase the disease becomes disseminated through the motor system. The mode of acquisition of the disease, its relation to a possible genetic factor, and the processes leading to tolerance, to latency or progression, to the relative involvement of upper and lower motor neurons, to involvement of spinocerebellar pathways, and to asymmetry are fundamental problems in understanding the disease.